Konsumerisme, Etika Romantis, dan Kultus Diri: Telaah Ringkas Pemikiran Colin Campbell - Indra Setia Bakti; M Husen; Amiruddin Ketaren (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2022)
Consumerism is a prevalent phenomenon that is already symptomatic in today's society. This study aims to discuss an ethic that supports the existence of a consumer society that was born and developed in a very long historical process. Colin Campbell was the first to speak of the romantic ethic that underlies the consumer society. This study uses the method of literature review. The main reference used is a book written by Campbell entitled